Quantitative study on product damages at Hitachi Transport System ((M) Sdn. Bhd. warehouse, Bandar Baru Bangi Selangor Darul Ehsan / Musrizalie Abd. Mutalip - Abd. Mutalip, Musrizalie (1996)
Most of the warehouse operators world-wide, have experienced product damages problems. Whenever the matter occurs, it then will result in losses to both operator and the manufacturer of that particular products stored in the warehouse . For instance, if such damages occurred, the operator have to make a report in order to investigate as well as to inform why or what are the reasons it was happened. This situation will incur extra costs to the operator if found guilty, thus in this case they are required to compensate the manufacturer (insured party).